(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The revolution in the automobile industry and liberalisedeconomy has led to tremendous increase in the vehicle ownership levels. Thishas resulted in changing traffic characteristics on road network. In this paperan attempt has been made to analyse the changing traffic composition trends,speed characteristics and travel patterns of Delhi. Delhi is a fast growing city, which over the years hasundergone landmark change in the characteristic of its transportationsector. Development and urbanizationover the past decade has led to rapid increase in the population of Delhi, themetropolitan city of India. Consequently, there has been a tremendous increasein the number of vehicles, which are causing very high. This Paperattempts to appreciate the problems & the critical issues in the traffic& transportation sector of the city. Further it attempts at proposingsolutions to improve and manage the system in the coming years. oxides (NOX),sulfur dioxide (SO2), volatile organic compounds (VOCs), particulate levels ofair pollution. Vehicular emissions are becoming most predominant source of airpollution in Delhi.